In Silico Study of Brazilin from Secang Wood (Caesalpinia Sappan L) as a Candidate for Splenomegaly Therapy - Youngest, Racy; Rusdianto, Rusdianto; Kamisah, Yusof; Maskoen, Ani Melani; Safitri, Ratu (Universitas 'Aisyiyah Yogyakarta, 2025)
Brazilin is a flavonoid found in secang (sappan) wood extract (Caesalpinia sappan L) currently undergoing clinical trials in phase 2 for the treatment of thalassemia patients. It is recognized for its antioxidant effects and its efficacy as a strong iron chelator, facilitating the binding and excretion of excess iron in the bloodstream of patients with thalassemia. This flavonoid compound may serve as a Janus kinase 2 (JAK2) inhibitor through the EPO/EPOR/JAK2/STAT5 pathway, which is responsible for splenomegaly (enlarged spleen). This study aims to investigate the mechanism by which sappan wood metabolite chemicals (brazilin) inhibit JAK2 in silico. This inhibition is expected to reduce splenomegaly in thalassemia patients and serve as an alternative to ruxolitinib (conventional medications). The pharmacokinetic profile of the ligand is predicted according to Lipinski's rule, while the binding energy (ΔG), initiation constant, and chemical bonds are examined using molecular docking with AutoDock v.4.25. This study successfully determined that brazilin, with a binding energy of -8.37 kcal/mol, is comparable to ruxolitinib, which has a binding energy of -8.71 kcal/mol. This finding shows that brazilin derived from sappan wood contains bioactive chemicals with potential JAK2 inhibitory activities. This finding establishes a foundation for further research aimed at developing new therapeutic agents for the treatment of splenomegaly in β-thalassemia and associated disorders.